Ciudad y texto: leyendo a Montserrat Roig en compañía de Cristina de Pizán - Łuczak, Barbara (Studia Romanica Posnaniensia, 2013)
In the article we study two visions of the city. A “classical” and allegorical one is included in Christine de Pizan’s well-known oeuvre, Le Livre de la Cité des Dames (1404/1405). We compare it to a biographically conditioned construction from the essays "Digues que m’estimes encara que sigui mentida" (1991) by the Catalan writer Montserrat Roig. The key factor in our analysis is the chronotope structure and the relationship between the image of the city and the writing act. We note a number of similarities between the two visions, some of them stemming from the identity and the social and cultural situation of the feminine subject, but also point out some differences, as those determined by the historical context of both texts and their literary genres.